The toll interleukin-1 receptor (IL-1R) 8/single Ig domain IL-1R-related molecule modulates the renal response to bacterial infection - Leemans, Jaklien C; Butter, Loes M; Teske, Gwendoline J D; Stroo, Ingrid; Pulskens, Wilco P; Florquin, Sandrine (Infection and immunity, 2012)
Our immune system has to constantly strike a balance between activation and inhibition of an inflammatory response to combat invading pathogens and avoid inflammation-induced collateral tissue damage. Toll interleukin-1 receptor 8 (IL-1R-8)/single Ig domain IL-1R-related molecule (TIR8/SIGIRR) is an inhibitor of Toll-like receptor (TLR)/IL-1R signaling, which is predominantly expressed in the kidney. The biological role of renal TIR8 during infection is, however, unknown. We therefore evaluated renal TIR8 expression during Escherichia coli pyelonephritis and explored its role in host defense using TIR8(-/-) versus TIR8(+/+) mice. We found that TIR8 protein is abundantly present in the majority of cortical tubular epithelial cells. Pyelonephritis resulted in a significant downregulation of TIR8 mRNA in kidneys of TIR8(+/+) mice. TIR8 inhibited an effective host response against E. coli, as indicated by diminished renal bacterial outgrowth and dysfunction in TIR8(-/-) mice. This correlated with increased amounts of circulating and intrarenal neutrophils at the early phase of infection. TIR8(-/-) tubular epithelial cells had increased cytokine/chemokine production when stimulated with lipopolysaccharide (LPS) or heat-killed E. coli, suggesting that TIR8 played an anti-inflammatory role during pathogen stimulation by inhibiting LPS signaling. These data suggest that TIR8 is an important negative regulator of an LPS-mediated inflammatory response in tubular epithelial cells and dampens an effective antibacterial host response during pyelonephritis caused by uropathogenic E. coli.